Synergistic Antibacterial Action of Norfloxacin-Encapsulated G4 Hydrogels: The Role of Boronic Acid and Cyclodextrin - Monica-Cornelia Sardaru; Irina Rosca; Simona Morariu; Elena-Laura Ursu; Alexandru Rotaru (Gels)
In this present study, we developed and characterized a series of supramolecular G4 hydrogels by integrating β-cyclodextrin (β-CD) and boronic acid linkers into a supramolecular matrix to enhance antibacterial activity against Staphylococcus aureus (S. aureus). We systematically investigated how varying the number of free boronic acid moieties (ranging from two to six), along with guanosine and β-CD content, influences both the structural integrity and antimicrobial efficacy of these materials. Comprehensive characterization using FTIR, circular dichroism, X-ray diffraction, SEM, AFM, and rheological measurements confirmed successful synthesis and revealed that higher boronic acid content correlated with a stronger, more organized network. The most effective hydrogel displayed an inhibition zone of 25 mm in disk diffusion assays, and was further explored as a drug delivery platform, with the aim to exploit the capacity of the free β-CD cavity of the hydrogels to incorporate hydrophobic drugs. Norfloxacin (Nfx), a poorly water-soluble antibiotic, was successfully encapsulated within the hydrogel matrix through the inclusion of complex formation with β-CD, improving its solubility and enabling sustained, targeted release. The Nfx-loaded hydrogel expanded the inhibition zone to 49 mm and completely eradicated S. aureus cells within 24 h, outperforming both the unloaded hydrogel and free Nfx. These results highlight the synergistic effect of boronic acid moieties and controlled drug release, underlining the potential of these hydrogels as versatile platforms for localized antimicrobial therapy, such as in wound dressings or implant coatings. Nevertheless, further in vivo studies and long-term stability assessments are needed to fully establish clinical relevance, safety, and scalability before these systems can be translated into routine healthcare applications.